Using of tactical and communication activities by the polygraph-experts during the instrumental diagnos-tics of reliability of the verbal information - Мотлях, Олександр Іванович; Потильчак, Анна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article discusses issues concerning the using of tactical communication activities by the polygraph-experts to participants of the psycho-physiological examination to verify the verbal information regarding the event of crime. The authors define the features of tactical communications activities, as well as proposing concrete ways of their improving.